Blue light excited quantum dot lens and preparation method thereof

By coating the surface of quantum dot lenses with a hydrophobic coating containing composite resin, curing agent, fluorinated resin and modified silica, the problem of quantum dot lenses being susceptible to water vapor corrosion is solved, achieving good hydrophobic and heat resistance properties and extending service life.

CN121679773APending Publication Date: 2026-03-17NANTONG VEEYEE NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511848461.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-09
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Existing quantum dot lenses are susceptible to moisture corrosion, leading to oxidation and quenching, decreased light efficiency, and easy contamination of the surface, which affects their service life. Existing improvement solutions are either costly or have limited effectiveness.

Method used

A hydrophobic coating containing composite resin, curing agent, fluorinated resin and modified silica is applied to the lens surface to form a hydrophobic coating. The synergistic effect of fluorinated resin and modified silica is used to improve water resistance and enhance mechanical and heat resistance.

Benefits of technology

It significantly improves the lens's water resistance and mechanical strength, enhances its hydrophobicity and heat resistance, and extends its service life.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a blue light excited quantum dot lens and a preparation method thereof, the blue light excited quantum dot lens comprises a lens body and a hydrophobic coating, the hydrophobic coating is formed by coating the surface of the lens body with a hydrophobic coating, and the hydrophobic coating comprises composite resin, a curing agent, fluorine-containing resin and modified silicon dioxide. The surface of the lens body is coated with the hydrophobic coating containing the composite resin, the curing agent, the fluorine-containing resin and the modified silicon dioxide, the hydrophobic coating is formed, the fluorine-containing resin increases the contact angle on the surface of the hydrophobic coating, the fluorine-containing resin and the modified silicon dioxide act synergistically, and the water resistance of the lens is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of quantum dot lenses, and in particular to a blue light-excited quantum dot lens and a method for its fabrication. Background Technology

[0002] Quantum dot lenses are innovative products that combine quantum dot materials with optical lens technology. They are mainly used to improve the color gamut and efficiency of optical systems. The core principle is to use quantum dot materials to convert light of a specific wavelength into three primary colors, thereby enhancing light processing capabilities.

[0003] Existing quantum dot lenses are typically made of polymer resin matrices (such as PMMA, polyurea, etc.), which have high surface energy and readily adsorb moisture and pollutants from the air. Moisture infiltration and adhesion can cause a series of problems: First, water molecules may gradually penetrate into the lens, directly attacking the quantum dots and causing oxidation and quenching, resulting in a rapid decrease in luminous efficacy and chromaticity; second, in humid environments, water vapor easily forms on the lens surface, affecting light transmittance and light output quality; finally, the surface's susceptibility to contamination increases the difficulty of cleaning and maintenance, impacting the reliability and lifespan of the end product.

[0004] While optimizing the matrix resin itself can improve overall water resistance to some extent, this is often costly or has limited effect. Therefore, there is an urgent need for a solution that can fundamentally isolate moisture erosion and endow the lens surface with durable and excellent hydrophobic properties. Summary of the Invention

[0005] To improve the heat resistance of quantum dot lenses, this application provides a blue light-excited quantum dot lens and its preparation method.

[0006] Firstly, this application provides a blue light-excited quantum dot lens, which employs the following technical solution: A blue light-excited quantum dot lens includes a lens body and a hydrophobic coating. The hydrophobic coating is formed by coating a hydrophobic paint onto the surface of the lens body. The hydrophobic coating includes a composite resin, a curing agent, a fluorinated resin, and modified silica.

[0007] By adopting the above technical solution, a hydrophobic coating is applied to the lens surface to form a hydrophobic coating. The fluorinated resin in the hydrophobic coating is enriched on the coating surface, which significantly improves the contact angle of the hydrophobic coating, thereby improving the water resistance of the lens. At the same time, modified silica is also added to the hydrophobic coating. The modified silica can be uniformly dispersed in the coating system and construct a micron-nano scale system on the coating surface, further enhancing the hydrophobic properties. Meanwhile, the interfacial compatibility between the fluorinated resin and the modified silica is stable, which synergistically improves the hydrophobic properties of the system. In addition, it has good heat resistance and strength, thereby improving the heat resistance and mechanical properties of the lens.

[0008] Preferably, the fluorinated resin is prepared by the following method: Butyl acetate, ethyl nonafluorobutyl ether, and perfluorohexyl ethyl acrylate were mixed to obtain a mixed solution. Methyl acrylate, acrylic cage-like polysilsesquioxane, KH570, and perfluoropolyether (meth) acrylate were mixed to obtain a polymerizable monomer. Part of the mixed solution was heated, and then 2,2'-azobisisobutyronitrile was added to obtain a preform. The remaining mixed solution was added to the polymerizable monomer to ensure uniform dispersion, and then added to the preform. The reaction was stirred, and after the reaction was completed, a fluorinated resin was obtained.

[0009] By adopting the above technical solution, both perfluorohexyl ethyl acrylate and perfluoropolyether (meth) acrylate are fluorinated monomers with low surface energy, which improves the hydrophobic properties of the system. Acrylic cage-like polysilsesquioxane serves as an inorganic skeleton to connect the components, thereby improving the overall mechanical strength and bonding tightness of the coating. Hydroxypropyl acrylate provides active hydroxyl groups to achieve crosslinking, ultimately yielding a fluorinated resin with good mechanical strength and hydrophobic properties, and giving the matrix components good bonding stability.

[0010] Preferably, the mass ratio of the acrylic cage-like polysilsesquioxane, hydroxypropyl acrylate and perfluoropolyether (meth)acrylate is (19-21):1:7.5.

[0011] By adopting the above technical solution, the mass ratio between acrylic cage-like polysilsesquioxane, hydroxypropyl acrylate and perfluoropolyether (meth)acrylate is preferably within the above range, so that the system crosslinks more fully and the system stability reaches a balance, and the hydrophobic coating prepared has good adhesion.

[0012] Preferably, the proportion of 2,2'-azobisisobutyronitrile is 0.9-1.1 wt% of the total amount of polymerizable monomers.

[0013] By adopting the above technical solution, and preferably having the proportion of 2,2'-azobisisobutyronitrile within the above range, the prepared system is more stable and the polymer formed is more uniform, which improves the overall stability and adhesion performance of the prepared hydrophobic coating, thereby improving the overall mechanical strength and durability of the lens.

[0014] Preferably, the modified silica is prepared by the following method: Anhydrous ethanol was mixed with water, then hexadecyltrimethoxysilane and tetraethyl orthosilicate were added. While maintaining stirring, ammonia was added, and the mixture was stirred in a water bath for 2 hours. After centrifugation and washing, the modified silica was obtained by drying.

[0015] By adopting the above technical solution, the methoxy group of hexadecyltrimethoxysilane reacts with the silanol group after hydrolysis of tetraethyl orthosilicate to graft long-chain alkyl groups onto the surface of silica particles, thereby giving silica good hydrophobic properties. The long alkyl chains on the surface of the modified silica enable silica to be well dispersed in the system and have good compatibility, reducing the agglomeration of the nano silica system. This results in a hydrophobic coating with good dispersibility. At the same time, the modified silica can synergistically improve the rigidity and heat resistance of the coating with the acrylic cage-like polysilsesquioxane in the fluorinated resin.

[0016] Preferably, the mass ratio of the tetraethyl orthosilicate to hexadecyltrimethoxysilane is 1:(0.14-0.16).

[0017] By adopting the above technical solution, the mass ratio between tetraethyl orthosilicate and hexadecyltrimethoxysilane is preferably within the above range. The hydrolysis rate of tetraethyl orthosilicate is stable, the generated silica particles are regular, and the modified silica particles have uniform particle size and good hydrophobic properties.

[0018] Preferably, the hydrophobic coating is prepared by the following method: Fluorine-containing resin and composite resin are mixed and stirred evenly. Modified silica and curing agent are then added and mixed evenly to obtain a hydrophobic coating.

[0019] By adopting the above technical solution, modified silica, fluorinated resin, composite resin and curing agent are mixed to prepare hydrophobic coatings with good hydrophobic properties and stability.

[0020] Preferably, the composite resin includes epoxy resin and phenolic resin.

[0021] By adopting the above technical solution, epoxy resin and phenolic resin are used as components of the mixed resin. Epoxy resin is a resin with excellent mechanical properties, corrosion resistance and chemical stability. Phenolic resin contains rigid benzene rings and has excellent thermal stability. When the two are mixed and then combined with fluorinated resin, the system has good adhesion, stability and heat resistance. After the combination and curing, it has good bonding performance and mechanical strength.

[0022] Preferably, the mass ratio of the composite resin, the fluorinated resin and the modified silica is 1.4:1:(0.08-0.12).

[0023] By adopting the above technical solution, and preferably within the above-mentioned range the mass ratio of composite resin, fluorinated resin and silica, the prepared hydrophobic coating has good stability.

[0024] Secondly, this application provides a method for fabricating a blue light-excited quantum dot lens, employing the following technical solution: A method for fabricating a blue light-excited quantum dot lens includes the following steps: The lens body is fixed on a spin coater, rotated, coated with a hydrophobic coating, left to stand, and then cured in an oven. After cooling, a hydrophobic coating is formed on the surface of the lens body, resulting in a blue light-excited quantum dot lens.

[0025] In summary, this application includes at least one of the following beneficial technical effects: 1. By coating the lens body surface with a hydrophobic coating containing composite resin, curing agent, fluorinated resin and modified silica to form a hydrophobic coating, the fluorinated resin increases the contact angle on the hydrophobic coating surface and works synergistically with the modified silica to improve the water resistance of the lens, while also giving the lens good heat resistance and mechanical properties. 2. Using butyl acetate and ethyl nonafluorobutyl ether as mixed solvents, methyl acrylate, acrylic cage-like polysilsesquioxane, hydroxypropyl acrylate, KH570, and perfluoropolyether (meth)acrylate as monomers, and AIBN as an initiator, a fluorinated resin was prepared. The resin polymerization was uniform, the system was fully cross-linked, and the stability was balanced. The adhesion, stability, and durability of the final hydrophobic coating were significantly improved, the mechanical strength of the lens was improved, and the lens had good hydrophobic properties. 3. Modified silica was prepared by using hexadecyltrimethoxysilane and tetraethyl orthosilicate under ammonia catalysis and water bath conditions. This allowed the long-chain alkyl groups of hexadecyltrimethoxysilane to be grafted onto the silica surface, thereby improving the overall hydrophobic properties of the system. At the same time, it reduced the aggregation of silica. The modified silica and the fluorinated resin synergistically improved the mechanical strength and heat resistance of the coating. Detailed Implementation

[0026] The present application will be further described in detail below with reference to the embodiments: Raw material description: All raw materials in the examples are commercially available; the molecular weight of perfluoropolyether (meth)acrylate is 1200 g / mol, and the curing agent is polyhexamethylene diisocyanate (CAS No.: 28182-81-2).

[0027] Example 1 Preparation of fluorinated resins: Butyl acetate (CAS No.: 123-86-4), ethyl nonafluorobutyl ether (CAS No.: 163702-05-4), and perfluorohexyl ethyl acrylate (CAS No.: 17527-29-6) were mixed in a mass ratio of 11:4:7 to obtain a mixed solution. Methyl acrylate, acrylic cage-like polysilsesquioxane (CAS No.: 1620202-27-8), KH570 (CAS No.: 2530-85-0), and perfluoropolyether (meth) acrylate were mixed to obtain polymerizable monomers. In the polymerizable monomers, the mass ratio between acrylic cage-like polysilsesquioxane, hydroxypropyl acrylate, and perfluoropolyether (meth) acrylate was 19:1:7.5, the mass ratio between hydroxypropyl acrylate, methyl acrylate, and KH570 was 1:0.22:1.27, and the mass ratio between the mixed solution and the polymerizable monomers was 1:1.36. A 30% (w / w) mixture was heated to 70°C and stirred for 10 min. Then, 2,2'-azobisisobutyronitrile (CAS No.: 78-67-1) was added, with the amount of 2,2'-azobisisobutyronitrile added being 0.9 wt% of the total amount of the monomers, to obtain a preform. The remaining mixture was added to the monomers to ensure uniform dispersion, and then added to the preform. The mixture was stirred and reacted at a constant temperature of 70°C for 4 h. After the reaction was completed, a fluorinated resin was obtained.

[0028] Preparation of modified silica: Mix 53g of anhydrous ethanol with 9g of deionized water, then add 1.23g of hexadecyltrimethoxysilane (CAS No.: 16415-12-6) and 8.77g of tetraethyl orthosilicate. Stir at 25°C for 15min, then add 2.18g of ammonia while maintaining stirring. Heat to 60°C in a water bath and stir for 2h. After washing with anhydrous ethanol by centrifugation, dry under vacuum in an oven at 65°C for 6h to obtain modified silica.

[0029] Preparation of hydrophobic coatings: 40g of epoxy resin and 10g of phenolic resin were mixed to obtain a composite resin. 20g of fluorinated resin and 28g of the composite resin were mixed and stirred evenly. Then, 1.6g of modified silica and 9.5g of curing agent were added and mixed evenly to obtain a hydrophobic coating.

[0030] Fabrication of blue light-excited quantum dot lenses: The lens body was ultrasonically cleaned in anhydrous ethanol for 10 minutes and dried with nitrogen. The lens body was then fixed on a spin coater and stirred at 500 rpm. Hydrophobic coating was added dropwise and the lens was rotated at 2000 rpm for 20 seconds. After coating, the lens body was left to stand at 25°C for 10 minutes. The coated lens body was then cured in an oven at 80°C for 1 hour. After cooling to room temperature, a hydrophobic coating was formed on the surface of the lens body, resulting in a blue light-excited quantum dot lens.

[0031] Example 2 Preparation of fluorinated resins: Butyl acetate, ethyl nonafluorobutyl ether, and perfluorohexyl ethyl acrylate were mixed in a mass ratio of 11:4:7 to obtain a mixed solution. Methyl acrylate, acrylate-based cage-like polysilsesquioxane, KH570, and perfluoropolyether (meth) acrylate were mixed to obtain polymerizable monomers. In the polymerizable monomers, the mass ratio between acrylate-based cage-like polysilsesquioxane, hydroxypropyl acrylate, and perfluoropolyether (meth) acrylate was 21:1:7.5, the mass ratio between hydroxypropyl acrylate, methyl acrylate, and KH570 was 1:0.22:1.27, and the mass ratio between the mixed solution and the polymerizable monomers was 1:1.36. A 30% mass mixture solution was heated to 70°C and stirred for 10 min. Then, 2,2'-azobisisobutyronitrile (2,2'-azobisisobutyronitrile) was added, with the amount of 2,2'-azobisisobutyronitrile added being 1.1 wt% of the total amount of the monomers, to obtain a preform. The remaining mixture solution was added to the monomers to ensure uniform dispersion, and then added to the preform. The mixture was stirred and reacted at a constant temperature of 70°C for 4 h. After the reaction was completed, a fluorinated resin was obtained.

[0032] Preparation of modified silica: Mix 53g of anhydrous ethanol with 9g of deionized water, then add 1.38g of hexadecyltrimethoxysilane and 8.62g of tetraethyl orthosilicate. Stir at 25°C for 15min, then add 2.18g of ammonia while maintaining stirring. Heat to 60°C in a water bath and stir for 2h. After washing with anhydrous ethanol by centrifugation, vacuum dry in an oven at 65°C for 6h to obtain modified silica.

[0033] Preparation of hydrophobic coatings: 40g of epoxy resin and 10g of phenolic resin were mixed to obtain a composite resin. 20g of fluorinated resin and 28g of the composite resin were mixed and stirred evenly. Then, 2.4g of modified silica and 9.5g of curing agent were added and mixed evenly to obtain a hydrophobic coating.

[0034] Fabrication of blue light-excited quantum dot lenses: The lens body was ultrasonically cleaned in anhydrous ethanol for 10 minutes and dried with nitrogen. The lens body was then fixed on a spin coater and stirred at 500 rpm. Hydrophobic coating was added dropwise and the lens was rotated at 2000 rpm for 20 seconds. After coating, the lens body was left to stand at 25°C for 10 minutes. The coated lens body was then cured in an oven at 80°C for 1 hour. After cooling to room temperature, a hydrophobic coating was formed on the surface of the lens body, resulting in a blue light-excited quantum dot lens.

[0035] Example 3 Preparation of fluorinated resins: Butyl acetate, ethyl nonafluorobutyl ether, and perfluorohexyl ethyl acrylate were mixed in a mass ratio of 11:4:7 to obtain a mixed solution. Methyl acrylate, acrylate-based cage-like polysilsesquioxane, KH570, and perfluoropolyether (meth) acrylate were mixed to obtain polymerizable monomers. In the polymerizable monomers, the mass ratio between acrylate-based cage-like polysilsesquioxane, hydroxypropyl acrylate, and perfluoropolyether (meth) acrylate was 20:1:7.5, the mass ratio between hydroxypropyl acrylate, methyl acrylate, and KH570 was 1:0.22:1.27, and the mass ratio between the mixed solution and the polymerizable monomers was 1:1.36. A 30% mass mixture solution was heated to 70°C and stirred for 10 min. Then, 2,2'-azobisisobutyronitrile (2,2'-azobisisobutyronitrile) was added, with the amount of 2,2'-azobisisobutyronitrile added being 1.0 wt% of the total amount of the monomers, to obtain a preform. The remaining mixture solution was added to the monomers to ensure uniform dispersion, and then added to the preform. The mixture was stirred and reacted at a constant temperature of 70°C for 4 h. After the reaction was completed, a fluorinated resin was obtained.

[0036] Preparation of modified silica: Mix 53g of anhydrous ethanol with 9g of deionized water, then add 1.3g of hexadecyltrimethoxysilane and 8.7g of tetraethyl orthosilicate. Stir at 25°C for 15min, then while maintaining stirring, add 2.18g of ammonia. Heat to 60°C in a water bath and stir for 2h. After washing with anhydrous ethanol by centrifugation, vacuum dry in an oven at 65°C for 6h to obtain modified silica.

[0037] Preparation of hydrophobic coatings: 40g of epoxy resin and 10g of phenolic resin were mixed to obtain a composite resin. 20g of fluorinated resin and 28g of the composite resin were mixed and stirred evenly. Then, 2g of modified silica and 9.5g of curing agent were added and mixed evenly to obtain a hydrophobic coating.

[0038] Fabrication of blue light-excited quantum dot lenses: The lens body was ultrasonically cleaned in anhydrous ethanol for 10 minutes and dried with nitrogen. The lens body was then fixed on a spin coater and stirred at 500 rpm. Hydrophobic coating was added dropwise and the lens was rotated at 2000 rpm for 20 seconds. After coating, the lens body was left to stand at 25°C for 10 minutes. The coated lens body was then cured in an oven at 80°C for 1 hour. After cooling to room temperature, a hydrophobic coating was formed on the surface of the lens body, resulting in a blue light-excited quantum dot lens.

[0039] Example 4 Example 4 is based on Example 3. In Example 4, when preparing the fluorinated resin, the mass ratio between acrylic cage-like polysilsesquioxane, hydroxypropyl acrylate and perfluoropolyether (meth)acrylate is 15:1:7.5.

[0040] Example 5 Example 5 is based on Example 3. In Example 5, when preparing the fluorinated resin, the mass ratio between acrylic cage-like polysilsesquioxane, hydroxypropyl acrylate and perfluoropolyether (meth)acrylate is 25:1:7.5.

[0041] Example 6 Example 6 is based on Example 3. In Example 6, the amount of 2,2'-azobisisobutyronitrile added during the preparation of the fluorinated resin is 0.7 wt% of the total amount of polymerizable monomers.

[0042] Example 7 Example 7 is based on Example 3. In Example 7, the amount of 2,2'-azobisisobutyronitrile added during the preparation of the fluorinated resin is 1.3 wt% of the total amount of polymerizable monomers.

[0043] Example 8 Example 8 is based on Example 3. In Example 8, no acrylic cage-like polysilsesquioxane was added when preparing the fluorinated resin.

[0044] Example 9 Example 9 is based on Example 3. In Example 9, when preparing modified silica, 0.99 g of hexadecyltrimethoxysilane and 9.01 g of tetraethyl orthosilicate were used.

[0045] Example 10 Example 10 is based on Example 3. In Example 10, when preparing modified silica, 1.6 g of hexadecyltrimethoxysilane and 8.4 g of tetraethyl orthosilicate were used.

[0046] Example 11 Example 11 is based on Example 3, except that hexadecyltrimethoxysilane is replaced with KH550.

[0047] Example 12 Example 12 is based on Example 3. In Example 12, 1g of modified silica was used in the preparation of the hydrophobic coating.

[0048] Example 13 Example 13 is based on Example 3. In Example 13, 3g of modified silica was used when preparing the hydrophobic coating.

[0049] Comparative Example 1 Comparative Example 1 is based on Example 3. In Comparative Example 1, when preparing the fluorinated resin, perfluorohexyl ethyl acrylate in the mixed solution was replaced with butyl acrylate, and perfluoropolyether (meth) acrylate in the polymer monomer was replaced with an equal amount of hydroxyethyl methacrylate.

[0050] Comparative Example 2 Comparative Example 2 is based on Example 3, except that the fluorinated resin is replaced with an equal amount of composite resin.

[0051] Comparative Example 3 Comparative Example 3 is based on Example 3, except that the modified silica is replaced with ordinary unmodified nano silica.

[0052] Performance testing The following performance tests were performed on the lenses of Examples 1-13 and Comparative Examples 1-3: (1) Hydrophobicity angle test The hydrophobic angle of the sample was tested using a contact angle measuring instrument, and the test results were recorded in Table 1.

[0053] (2) Heat resistance test With reference to GB / T 1634.2-2004 and GB / T 2423.2-2021, the heat resistance of the samples was tested. The aging temperature was 200℃, the aging time was 100h, the heating rate was 5℃ / min, and the samples were naturally cooled to 25℃ after aging. The yellowing index and light transmittance reduction rate of the samples were tested. Each sample was tested 3 times, and the average value was taken. The test results were recorded in Table 1.

[0054] (3) Mechanical strength test Using GB / T 6739-2021 as the testing reference, the hardness of the samples was tested. Each sample was tested three times, and the average value was taken. The test results were recorded in Table 1.

[0055] Table 1 Performance test results of Examples 1-13 and Comparative Examples 1-3 Testing items Hydrophobic angle / ° Yellowing index after heat aging Light transmittance reduction rate after thermal aging / % hardness Example 1 151 1.1 3.2 5H Example 2 152 1.0 3.0 5H Example 3 154 0.8 2.7 5H Example 4 148 1.8 4.1 3H Example 5 149 1.3 5.5 6H Example 6 150 2.5 6.8 3H Example 7 145 2.1 7.5 2H Example 8 128 4.5 12.2 2H Example 9 138 1.5 8.8 5H Example 10 152 1.7 4.3 4H Example 11 104 3.2 10.5 5H Example 12 142 1.6 4.5 3H Example 13 153 1.4 7.9 6H Comparative Example 1 82 3.8 16.5 3H Comparative Example 2 95 5.2 22.2 2H Comparative Example 3 125 1.9 20.5 4H As shown in Table 1, the hydrophobic angles of Examples 1-3 are all above 150°, indicating that the quantum dot lenses prepared in this application have good hydrophobic properties. After thermal aging, the yellowing index of Examples 1-3 is all 1.1 or below, and the light transmittance reduction rate is all 3.2% or below, indicating that the quantum dot lenses prepared in this application have good heat resistance. The hardness of Examples 1-3 is all 5H or above, indicating that the quantum dot lenses prepared in this application have good hardness.

[0056] In Examples 4 and 5, the mass ratios of acrylic-based cage-like polysilsesquioxane, hydroxypropyl acrylate, and perfluoropolyether (meth)acrylate during the preparation of the fluorinated resin were not within the range specified in this application. When the proportion of acrylic-based cage-like polysilsesquioxane was too low, the nano-roughness of the prepared hydrophobic coating surface decreased, making it difficult to further improve the overall hydrophobic properties of the system. At the same time, the overall stability of the prepared fluorinated resin also decreased, affecting the heat resistance and mechanical strength of the system. When the proportion of acrylic-based cage-like polysilsesquioxane was too high, the excessive acrylic-based cage-like polysilsesquioxane was difficult to disperse uniformly in the resin network system, causing the acrylic-based cage-like polysilsesquioxane to agglomerate in the system, resulting in decreased stability and excessively high crosslinking density, which affected the migration of fluorinated groups to the coating surface. Therefore, the properties of Examples 4 and 5 were all reduced.

[0057] In Examples 6 and 7, the amount of 2,2'-azobisisobutyronitrile used in the preparation of the fluorinated resin was not within the range specified in this application. When the amount of 2,2'-azobisisobutyronitrile added was too low, i.e., the initiator concentration of the system was too low, the molecular weight of the polymer was too large, the viscosity of the system was too high, the reaction was uneven, and the monomer conversion rate decreased. The hydrophobic coating would migrate and volatilize and decompose in the later stage of curing, destroying the stability of the coating and causing the performance to decline after thermal aging. When the amount of 2,2'-azobisisobutyronitrile added was high, i.e., the initiator concentration was too high, it would cause too many free radicals to be generated in the system, making it difficult to form a stable coating and to uniformly arrange them on the coating surface. As a result, the hydrophobic properties and stability of the system decreased. Therefore, the performance of Examples 6 and 7 both decreased.

[0058] In Example 8, the fluorinated resin did not contain acrylic-based cage-like polysilsesquioxane. The coating only improved the hydrophobicity of the system by modifying the roughness of silica, which was difficult to achieve a synergistic effect in improving the overall hydrophobicity of the coating system. At the same time, the fluorinated resin without the acrylic-based cage-like polysilsesquioxane structure could not form a more tightly bound network structure, and the system performance was damaged and degraded at high temperatures.

[0059] In Examples 9 and 10, the mass ratio between hexadecyltrimethoxysilane and tetraethyl orthosilicate during the preparation of modified silica was not within the range specified in this application. When the content of hexadecyltrimethoxysilane was too low, the surface of the generated silica particles still had hydrophilic groups, and the system still had hydrophilic properties, making it difficult to improve the hydrophobic properties. Furthermore, the compatibility decreased, and the overall stability of the coating decreased. When the content of hexadecyltrimethoxysilane was too high, the silica particles generated by tetraethyl orthosilicate were too small, and the stability decreased. Therefore, the performance of Examples 9 and 10 was reduced.

[0060] In Example 11, when preparing modified silica, hexadecyltrimethoxysilane was replaced with KH550. Although the introduction of amino groups in KH550 can improve the dispersibility of silica and allow amino groups to better bond with epoxy resins, amino groups are hydrophilic groups. As a result, the hydrophobic properties of the hydrophobic coating are lost, and yellowing occurs at high temperatures, leading to a decrease in both hydrophobic properties and temperature resistance.

[0061] In Examples 12 and 13, the mass ratio of the composite resin, fluorinated resin, and modified silica during the preparation of the hydrophobic coating is not within the range specified in this application. When the content of modified silica is too low, the hydrophobic structure decreases, and it can stably combine with the fluorinated resin to achieve stable hydrophobic properties. When the content of modified silica is too high, the excess silica will agglomerate in the system, and too much silica will affect the overall light transmittance of the system and decrease its stability.

[0062] In Comparative Example 1, no fluorine-containing system was added during the preparation of the fluorinated resin. The hydrophobic properties of the prepared resin system decreased, and CF bonds were indeed formed. The performance of the resin matrix decreased at high temperatures. At the same time, the compatibility between the system and the acrylic cage-like polysilsesquioxane was too low, and the overall stability of the coating system decreased. Therefore, the performance of Comparative Example 1 decreased.

[0063] In Comparative Example 2, the fluorinated resin was replaced with an equal amount of composite resin. After the absence of fluorinated segments and acrylic cage-like polysilsesquioxane system, the ordinary resin system could not effectively improve the hydrophobicity of the system by modifying silica alone. Moreover, the high temperature resistance of the system decreased, and the interfacial bonding performance could not be further improved.

[0064] In Comparative Example 3, no modification was made to the silica. The unmodified silica agglomerated in the system, resulting in decreased stability of the prepared hydrophobic coating and making it difficult to synergistically improve the hydrophobic properties of the system with the fluorinated resin.

[0065] This specific embodiment is merely an explanation of this application and is not intended to limit it. Based on the above description, those skilled in the art can make various changes and modifications without departing from the technical concept of this application. The technical scope of this application is not limited to the contents of the specification but must be determined according to the scope of the claims.

Claims

1. A blue light excited quantum dot lens, characterized in that: The lens body and the hydrophobic coating are formed by coating a hydrophobic coating on the surface of the lens body, and the hydrophobic coating comprises a composite resin, a curing agent, a fluorine-containing resin and modified silica.

2. The blue excitation quantum dot lens of claim 1, wherein: The fluorine-containing resin is prepared by the following method: Butyl acetate, ethyl nonafluorobutyl ether and perfluorohexyl ethyl acrylate are mixed to obtain a mixed solution, methyl acrylate, acrylic cage polysilsesquioxane, KH570 and perfluoropolyether (meth) acrylate are mixed to obtain a polymerization monomer; part of the mixed solution is heated, then 2,2'-azobis isobutyronitrile is added to obtain a preform; the remaining mixed solution is added to the polymerization monomer to make the polymerization monomer uniformly dispersed, then added to the preform, stirred and reacted, and the fluorine-containing resin is obtained after the reaction is completed.

3. The blue excitation quantum dot lens of claim 2, wherein: The mass ratio of the acrylic cage polysilsesquioxane, hydroxypropyl acrylate and perfluoropolyether (meth) acrylate is (19-21):1:7.

5.

4. The blue excitation quantum dot lens of claim 2, wherein: The proportion of 2,2'-azobis isobutyronitrile is 0.9-1.1wt% of the total amount of the polymerization monomer.

5. The blue excitation quantum dot lens of claim 1, wherein: The modified silica is prepared by the following method: Anhydrous ethanol and water are mixed, then hexadecyl trimethoxysilane and tetraethyl orthosilicate are added under stirring, ammonia water is added, stirred under water bath condition, then centrifuged and washed, and dried to obtain the modified silica.

6. The blue excitation quantum dot lens of claim 5, wherein: The mass ratio of the tetraethyl orthosilicate and the hexadecyl trimethoxysilane is 1:(0.14-0.16).

7. The blue excitation quantum dot lens of claim 1, wherein: The hydrophobic coating is prepared by the following method: The fluorine-containing resin and the composite resin are mixed and stirred uniformly, then the modified silica and the curing agent are added and mixed uniformly to obtain the hydrophobic coating.

8. The blue excitation quantum dot lens of claim 7, wherein: The composite resin comprises an epoxy resin and a phenolic resin.

9. The blue excitation quantum dot lens of claim 8, wherein: The mass ratio of the composite resin, the fluorine-containing resin and the modified silica is 1.4:1:(0.08-0.12).

10. A method for preparing the blue light excited quantum dot lens according to any one of claims 1-9, characterized in that: The following steps are included: The lens body is fixed on a spin coater, the spin coater is started to rotate, the hydrophobic coating is coated, and the coated lens body is placed in an oven for curing after coating, then cooled to form a hydrophobic coating on the surface of the lens body, and a blue light excited quantum dot lens is obtained.